Pluralitas Mesir dalam Imarah Yakubian: Dialogisme Bakhtin dalam Novel Al-Aswany - Herpin Nopiandi Khurosan (SULUK: Jurnal Bahasa, Sastra, dan Budaya, 2021)
Al-Aswany is known as the writer who often calls for Egyptian democracy. In his creative work, al-Aswany made the themes of democracy, freedom of speech, equality of rights and so on. The various thematic (democracy) in Bakhtin terms are called carnivalistic and/or polyphonic, have many voices. In this paper the author will map carnivalistics/polyphonic through the novel Imarah Yakubian written by al-Aswany. The carnivalism and polyphony of the Jacobian Empire are tested by Bakhtin's dialogic theory. The elements studied include: 1) carnivalization, 2) composition of the polyphonic novel, 3) character and author position, 4) dialogue of the novel consisting of: a) dialogue between characters; b) representation of ideas; and c) intertextual dialogue. As a result, the Jacobian Imarah can be categorized as a polyphonic novel with predominantly carnivalistic features. In the novel there are many dialogical voices. The dialogue is in the form of dialogue between figures as well as dialogue between novel texts (Imarah Yakubian) and other texts.